RESPONDING TO THE COVID 19 PANDEMIC IN A RESOURCE CONSTRAINED COUNTRY: THE CASE OF PAKISTAN - Iqbal, Meesha; Zahidie, Aysha; Jumani, Yusra; Asif, Saima; Shahid, Babar (Journal of Ayub Medical College Abbottabad, 2021)
Background: Pakistan, like the rest of the world has not been spared by COVID-19, with the cases escalating nationwide. Being a developing country, Pakistan has had meagre resources and weak health systems to tackle the menace. We analysed the national response of Pakistan to the pandemic by critically analysing the interventions taken at community, health systems and multi-sectoral level and identifying the response gaps. The fragile health system of Pakistan performed fairly well according to its ability - the bed capacity was expanded, health professionals’ capacity building strategies were adopted, telemedicine was put into practice, indigenous production of required personal protective equipment started, testing capacity was increased, and attempts were made to improve the surveillance mechanisms. However, the strategies adopted at the community level proved in-adequate. The severity of the disease was not communicated clearly to the public, religious leaders were not effectively on board, social distancing measures were not strictly followed specially during religious festivities, contact tracing was not extensively carried out specially in the rural areas - overall awareness of the community to COVID-19 remained low. The educational institutions were closed in time but the intermittent lockdown procedures and easing of transport restrictions led to community spread of the virus. Overall, Pakistan’s performance has been acceptable, but community engagement and participation need to be improved.